Development of Teaching Supplement “RESe-CIG” to Improve Understanding of Respiratory System Concepts and Attitudes towards the Dangers of Vaping - Salsabila, Fitriana; Lisdiana (Journal of Biology Education, 2024)
Cases of e-cigarette use at the youth level have increased, this proves students' lack of knowledge and caring attitude regarding the dangers of vaping. This research aims to develop a teaching supplement "RESe-CIG" to increase understanding of respiratory system concepts and awareness of the dangers of vaping. This research is Research and Development (R&D) research referring to the steps (1) potential problems, (2) information gathering, (3) product design, (4) design validation, (5) design revision, (6) trial small scale, (7) product revision, (8) large scale trial, (9) product revision, (10) final product. The research data is in the form of feasibility data, product effectiveness data in increasing understanding of concepts, as well as a caring attitude towards the dangers of vaping. All three were analyzed using quantitative and qualitative descriptive methods. The research results show that the "RESe-CIG" teaching supplement is suitable for use as teaching material for the respiratory system with media validity of 95%, material validity of 96.8%, teacher response of 92.5%, and student response of 95%. The application of the "RESe-CIG" teaching supplement as respiratory system teaching material effectively increases understanding of concepts with an N-Gain in the high category of 66% and the medium category of 22% with an average N-Gain of 0.71. The application of the "RESe-CIG" teaching supplement as a respiratory system teaching material effectively increases attitudes towards the dangers of vaping with an N-Gain in the high category of 47% and the medium category of 37% with an average N-Gain of 0.55. Based on the research results, it can be concluded that the development of the "RESe-CIG" teaching supplement is feasible and effective in increasing understanding of concepts and attitudes regarding the dangers of vaping.